Utility Of Platelet Indices In Dengue Seropositive Patients: An Observational Study At A Tertiary Care Hospital (Journal of Pharmaceutical Negative Results, 2023)
Dengue, also known as breakbone fever, is an emerging mosquito borne viral illness of tropical and subtropical areas of the world today. It is caused by one of the four serotypes of the dengue virus (DEN-1,DEN-2,DEN-3,DEN-4) also referred to as an arbovirus (arthropod-borne viruses) that belongs to the genus flavivirus of the family flaviviridae. It is transmitted by mosquitoes of the genus Aedes aegypti.[1]